Method for measuring cohesive binding energy of organic cementing material based on energy balance method
Through energy balance method and pulling strength test, an internal and external energy balance formula for organic gelling materials was established, which solved the harsh and unstable test conditions of the cohesive binding energy determination method of organic gelling materials in the prior art, and achieved quick Accurate and universal cohesive binding energy determination.
Patent Information
- Application Number
- CN202411276094.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-01-10
AI Technical Summary
The existing cohesive bonding energy determination methods for organic gelling materials have problems such as harsh test conditions, complex operation and unstable test results. They are mainly due to the reliance on microscopic contact angle indicators, which are greatly affected by external factors, and require a variety of test reagents and strictness. temperature control.
Using the energy balance method, the internal and external energy balance formula is established through the correlation formula between the pulling strength of organic gelled materials and the cohesive binding energy, and the material pulling strength test is used to establish the internal and external energy balance formula, simplify the operation, reduce the test difficulty, and improve the test stability. sex.
It realizes the quick determination of the cohesive binding energy of organic gelling materials, with loose test conditions, low difficulty and high stability. It is suitable for testing of a variety of materials and has excellent universality and accuracy.
Smart Images

Figure CN119290738A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical material testing, in particular to a method for determining the cohesive binding energy of an organic gelling material based on an energy balance method. Background Art
[0002] Organic cementitious materials refer to a type of cementitious materials based on natural or synthetic polymer compounds, among which asphalt, resin and rubber are the most commonly used. Under physical and chemical effects, the material can be transformed from a slurry into a solid stone-like body, and can bond other materials to form a composite solid substance with a certain mechanical strength. Thanks to its ability to bond other materials, organic cementitious materials are widely used in many important fields such as construction, roads and chemicals. For example, asphalt materials are often used to bond crushed stone aggregates and ore powders of different particle sizes in a certain ratio to form asphalt mixtures to carry road traffic loads and resist adverse climatic effects; resins are often mixed with curing agents and sand and gravel to form polymer concrete, which has excellent properties such as fast hardening, high strength and durability compared to ordinary cement concrete. In the process of organic cementitious materials playing a bonding role, their own cohesive properties (the ability of organic cementitious materials to wrap other materials) are directly related to the performance of the composite. Therefore, how to accurately quantify and evaluate the cohesive properties of organic cementitious materials and use this to design a material blending ratio combination that meets various specific application scenarios has always been a hot issue in the promotion and application of organic cementitious materials.
[0003] At present, the mainstream test method for the cohesive performance of organic gelling materials is: select a variety of auxiliary test reagents with known material properties, measure the stable contact angle between the organic gelling material and the auxiliary test reagents by the plug-in method or the drop method, calculate the surface energy of the organic gelling material based on the material surface energy theory, substitute it into the corresponding formula to further solve the cohesive binding energy, and use it to characterize the cohesive performance of the organic gelling material. The advantages of this test method are: (1) The obtained cohesive binding energy can be used as an evaluation index of organic gelling materials to guide the material and structural composition design of various organic gelling material composites; (2) Based on the cohesive binding energy, a mechanical model can be established to evaluate the self-healing, fatigue cracking and other properties of organic gelling materials and their composites; (3) The cohesive binding energy can be linked to the actual service performance of the material to achieve cross-scale design and evaluation of materials.
[0004] However, the above test methods have the problems of harsh test conditions, complicated operation process and unstable test results when obtaining the cohesive binding energy of organic gelling materials. The specific reasons are as follows:
[0005] (1) Both the plug-in method and the drop method require the measurement of the stable contact angle between the organic gelling material and the known test reagent, so as to calculate the surface energy of the material, and substitute it into the corresponding formula to solve for the cohesive binding energy. However, as a microscopic test indicator, the contact angle is easily affected by external and human factors. Small disturbances (such as temperature, inclination, etc.) and different measurement times may cause huge differences in the results.
[0006] (2) Both the plug-in plate method and the droplet method require at least three test reagents with known surface energy parameters. The same test is carried out on the same organic gelling material to test the stable contact angle formed between each reagent and the organic gelling material. Only then can the surface energy parameters of asphalt be obtained by solving the simultaneous equations. This means that the requirements for test conditions, test materials and test techniques are very high.
[0007] (3) The plug-in method and the drop method are greatly affected by the test temperature. The surface energy parameters of the organic gelling material obtained at different test temperatures may be significantly different. Therefore, each link of the test needs to be maintained at a uniform and constant test temperature. In addition, the commonly used test reagents (such as distilled water, ethylene glycol, etc.) have a low density and are easy to volatilize, especially at high temperatures, which will significantly affect the measurement of the contact angle; the test reagents with higher density are easily affected by their own weight, which will also affect the measurement of the contact angle, thereby affecting the measurement accuracy of the surface energy.
[0008] In summary, the traditional method for determining the cohesive binding energy of organic gelling materials has certain defects. The main problem comes from the use of the contact angle as a microscopic indicator to calculate the surface energy parameters. It requires sophisticated test operations and strict conditions for the test to be successful. Summary of the invention
[0009] The technical problem to be solved by the present invention is to address the deficiencies of the above-mentioned prior art and to provide a method for determining the cohesive binding energy of an organic gelling material based on the energy balance method. From the perspective of the internal and external energy balance of the organic gelling material, this determination method establishes a relationship formula between the macroscopic index of the material's tensile strength and the microscopic index of the material's cohesive binding energy. Compared with traditional testing methods, this method greatly relaxes the test conditions, simplifies the operation process, reduces the test difficulty, and improves the test stability.
[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0011] A method for determining the cohesive binding energy of an organic gelling material based on an energy balance method comprises the following steps:
[0012] Step 1: Establish the internal and external energy balance formula of organic gelling materials:
[0013]
[0014] Wherein, U represents the total energy required for the fracture of the organic gelling material, P represents the external force applied to the organic gelling material, △h represents the displacement of the organic gelling material along the direction of the external force, ε represents the strain generated by the unit cell of the organic gelling material, σ represents the stress generated by the unit cell of the organic gelling material, V represents the total volume of the organic gelling material, S represents the average cross-sectional area of the organic gelling material, and △G represents the cohesive binding energy of the organic gelling material;
[0015] Step 2, preparing an organic gelling material film: first preheat the organic gelling material to be tested to the melting temperature to form a flowable liquid material, and then pour the liquid material into a cylindrical material mold preheated to the same temperature as the material to form an organic gelling material film; wherein the cylindrical material mold can be opened and closed and dismantled, and the inner diameter is r; the mass of the poured organic gelling material is m, and the density is ρ; the thickness h of the organic gelling material film can be controlled by the following formula:
[0016] h=m / ρπr 2 ;
[0017] Step 3, determining the suitable thickness of the organic gelling material film: after forming n groups of organic gelling material films of different thicknesses according to step 2, use a material pull-out strength tester to test the pull-out strength of each group of organic gelling material films formed until the corresponding organic gelling material film is completely broken, and then judge the fracture state on both sides of the fracture surface of the organic gelling material film to select an organic gelling material film of suitable thickness from the n groups of organic gelling material films of different thicknesses; a total of x organic gelling material films are selected, and the thickness order is h p1 、h p2 ......h px , where x≥3;
[0018] Step 4: Pull-out strength test of organic cementitious materials: Form the organic cementitious materials into appropriate thickness h according to step 2. p1 、h p2 ......h px After the organic gelling material film is formed, a material pull-out strength tester is used to test the pull-out strength of each group of organic gelling material films until the corresponding organic gelling material film is broken; in this process, a strain-stress curve of the corresponding organic gelling material film is constructed, and the ultimate pull-out strength σ of the organic gelling material is obtained based on the constructed strain-stress curve max As well as the Young's modulus E of the organic cementitious material, the ultimate tensile strength σ of the organic cementitious material max is the peak stress value of the corresponding strain-stress curve, and the Young's modulus E of the organic cementitious material is the slope of the approximate straight line portion of the stress rising curve in the corresponding strain-stress curve;
[0019] Step 5: Based on step 1, step 4 and Griffith energy balance theory, calculate the cohesive binding energy of the organic gelling material. The specific process is as follows:
[0020] Step 501: Establish a calculation formula for the cohesive binding energy of the organic gelling material. The specific formula is as follows:
[0021]
[0022] In the formula, ΔG y is the cohesive binding energy of the organic gel material corresponding to the yth suitable thickness, λ y is the calibration coefficient corresponding to the yth suitable thickness, a and b are unknown coefficients, σ maxy is the ultimate tensile strength of the organic cementitious material corresponding to the yth suitable thickness, h py is the thickness of the organic gelling material film corresponding to the yth suitable thickness, E y is the Young's modulus corresponding to the yth suitable thickness, y = 1, 2...m;
[0023] Step 502, solve the unknown coefficients a and b: Based on step 501, take λy as the independent variable, ΔG y As the dependent variable, and taking the minimum variance of the cohesive binding energy of m organic gelling materials as the optimization goal, it is substituted into the numerical calculation software for nonlinear programming solution to obtain the unknown coefficients a and b;
[0024] Step 503, calculating the cohesive binding energy of the organic gelling material: Substitute the unknown coefficients a and b obtained in step 502 into the calculation formula in step 501, and take the average value of the cohesive binding energy of x organic gelling materials as the cohesive binding energy of the organic gelling material.
[0025] Preferably, in step 3, the thickness of the organic gelling material film is determined, which specifically includes the following steps:
[0026] Step 301, material preparation: forming n groups of organic gelling material films of different thicknesses according to step 2;
[0027] Step 302, compacting the organic gelling material film: placing the cylindrical material mold with the organic gelling material film directly below the drawing rod of the material pulling strength tester; the drawing rod is lowered, and the loading plate at the bottom of the drawing rod compacts the top surface of the organic gelling material film; then, the cylindrical material mold is removed in an opening and closing manner;
[0028] Step 303, pulling the organic gelling material film: the pulling rod is raised, and the loading plate pulls the organic gelling material film;
[0029] Step 304, the organic gelling material film is completely broken: the height of the pull plate rod continues to rise, and when the actual monitoring value of the stress sensor drops to 0, it is considered that the organic gelling material film is completely broken;
[0030] Step 305, determine the fracture state of the material: take photos to record the fracture surfaces on both sides of the organic gelling material film; perform grayscale processing on the image; if the fracture surfaces on both sides are complete and have no white spots, it is considered that the fracture only occurs inside the organic gelling material film, and the corresponding thickness of the organic gelling material film is taken as the appropriate thickness h p If any fracture surface is damaged and has white spots, repeat steps 301 to 305 until x different suitable thicknesses h are obtained. p1 、h p2 ......h px ; where x≥3.
[0031] Preferably, in step 4, the organic gelling material tensile strength test specifically comprises the following steps:
[0032] Step 401, material preparation: forming into suitable thickness h according to step 2 p1 、h p2 ......h px Organic gelling material film;
[0033] Step 402, repeating steps 302 to 303 for all the organic gelling material films formed in step 401;
[0034] Step 403, stress monitoring: during the process of the pull rod rising in height, a stress sensor is used to monitor the stress value per unit area of the bottom surface of the loading plate in real time;
[0035] Step 404, strain monitoring: during the process of the pull rod rising in height, a strain sensor is used to monitor in real time the ratio of the vertical displacement of the pull rod to the thickness of the asphalt film;
[0036] Step 405, constructing a strain-stress curve: using the strain monitored in step 404 as the abscissa and the stress monitored in step 403 as the ordinate to establish a strain-stress curve;
[0037] Step 406, obtaining the ultimate pull-out strength of the organic gelling material: the height of the pull-out rod continues to rise, and the strain-stress curve constructed in step 405 will have a stress peak value, which is the ultimate pull-out strength σ of the organic gelling material obtained. max ;
[0038] Step 407, internal fracture of the organic gelling material film: the height of the pulling rod continues to rise. When the actual monitoring value of the stress sensing sensor drops to 10% of the maximum pressure peak, it is considered that the organic gelling material film is fractured and the height of the pulling rod stops rising. At this time, the slope of the approximate straight line portion of the stress rise curve in the stress-strain curve is taken as the Young's modulus E of the organic gelling material.
[0039] Preferably, in step 2, the preheating temperature of the tested organic gelling material is the same as the preheating temperature of the cylindrical material mold, and both are not lower than the melting temperature of the organic gelling material.
[0040] Preferably, in step 3 and step 4, the drawing of the organic gelling material needs to be carried out in a constant temperature environment maintained at the test temperature ±5°C.
[0041] Preferably, in step 3 and step 4, the test temperature for drawing the organic gelling material cannot be higher than the melting point of the organic gelling material, nor lower than its glass transition temperature.
[0042] Preferably, in step three and step four, the height rising rate of the pulling rod is in the range of 10 to 20 mm / min.
[0043] Preferably, in step one, the cylindrical material mold includes a first material mold and a second material mold, two openings of which are oppositely arranged and both are semicircular.
[0044] Preferably, the cylindrical material mold is placed on a steel plate with a groove on the top surface; wherein the first material mold and the second material mold are both located in the groove of the steel plate and can open and close relative to each other.
[0045] Preferably, radial pull rods are provided on the outer sides of the first material mold and the second material mold, and the ends of the pull rods slide through the side walls of the grooves of the steel plates; by pulling the pull rods, the relative opening and closing of the first material mold and the second material mold can be achieved.
[0046] The present invention has the following beneficial effects:
[0047] (1) Based on the energy balance method, the present invention proposes a correlation formula between the pull-out strength and cohesive binding energy of organic cementitious materials. The microscopic cohesive binding energy index can be obtained through the macroscopic pull-out strength test of the material, thereby avoiding the problems of difficult operation and harsh test conditions in traditional microscopic contact angle tests, greatly relaxing the test conditions, reducing the test difficulty, and improving the test stability.
[0048] (2) The calculation formula for the cohesive binding energy of the organic gelling material proposed in the present invention introduces a calibration coefficient related to the thickness of the organic gelling material film, taking into account the effect of the thickness of the organic gelling material film on the ultimate tensile strength in the tensile strength test, thereby avoiding the situation where the cohesive binding energy calculated for different organic gelling material film thicknesses is too different, thereby improving the accuracy of the test.
[0049] (3) The test method proposed in the present invention is different from the traditional contact angle index in the selection of test targets. The ultimate pull-out strength of the organic gelling material selected in the present invention does not require additional auxiliary reagents and is less disturbed by the test temperature change. It is suitable for testing different organic gelling materials under high and low temperature conditions and has excellent test stability and universality.
[0050] (4) The method for determining the cohesive binding energy of organic cementitious materials proposed in the present invention theoretically establishes a formula for the internal and external energy balance of organic cementitious materials based on the energy balance method. Experimentally, a systematic test procedure for the cohesive binding energy of organic cementitious materials is given based on a pull-out strength test. The method is not only applicable to the determination of the cohesive binding energy of various organic cementitious materials, but should also be applicable to other materials with a cementing effect, and has excellent universality.
[0051] (5) The organic gelling material mold designed by the present invention is made of polytetrafluoroethylene material according to local conditions. The material has the characteristics of corrosion resistance, high temperature resistance and resistance to organic solvents, and is perfectly adapted to the test environment of the present invention. It can ensure that the organic gelling material in the molten state is well formed, avoid the adverse morphology of the material affecting the accuracy of the tensile strength test, and improve the success rate of the test.
[0052] In summary, the present invention can realize the rapid determination of the cohesive binding energy of organic gelling materials, has the advantages of loose test conditions, low test difficulty, high test stability and strong test universality, and is of great significance to the promotion and application of organic gelling materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 The flowchart of the method for determining the cohesive binding energy of organic gelling materials based on the energy balance method of the present invention is shown.
[0054] Figure 2 The schematic diagram of the structure of the material pulling strength tester in the present invention is shown.
[0055] Figure 3 A top view of a first material mold in the present invention is shown.
[0056] Figure 4 An example of a stress-strain curve constructed from a tensile strength test of an organic cementitious material using asphalt as an example is shown.
[0057] The components include: 1. constant temperature box; 2. servo motor; 3. pull rod; 4. loading plate; 5. stress sensor; 6. strain sensor; 7. test bench; 8. steel plate; 9. first pull rod; 10. second pull rod; 11. first material mold; 11-1. connecting groove; 12. second material mold. DETAILED DESCRIPTION
[0058] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific preferred embodiments.
[0059] In the description of the present invention, it should be understood that the terms "left side", "right side", "upper part", "lower part" and the like indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. "First", "second" and the like do not indicate the importance of the components, and therefore cannot be understood as limiting the present invention. The specific dimensions used in this embodiment are only for illustrating the technical solution, and do not limit the scope of protection of the present invention.
[0060] like Figure 2 As shown, the material pulling strength tester includes a constant temperature box 1, a pulling rod 3, a pulling drive device, a cylindrical material mold, a stress sensor 5, a strain sensor 6 and a steel plate 8.
[0061] The cylindrical material mold includes a first material mold 11 and a second material mold 12 .
[0062] The steel plate 8 is placed on the test bench 7, and a groove is provided on the top of the steel plate 8.
[0063] The drawing rod 3 , the cylindrical material mold, the test bench 7 and the steel plate 8 are all arranged in the constant temperature box 1 .
[0064] The first material mold 11 and the second material mold 12 are arranged horizontally in the groove of the steel plate 8, and are preferably as follows: Figure 3 The semicircular shape shown in the figure, wherein the first material mold 11 is preferably connected to the first tie rod 9 through the connecting groove 11-1, and the first tie rod 9 is slidably mounted on the left wall of the groove of the steel plate 8; the second asphalt mold 12 is preferably slidably mounted on the right wall of the groove of the steel plate 8 through the second tie rod 10. Both the first material mold 11 and the second material mold 12 are preferably made of polytetrafluoroethylene material, which has the characteristics of high temperature resistance, resistance to organic solvents and extremely low friction coefficient, can prevent corrosion by organic gelling materials, and avoid organic gelling materials from remaining on the mold, which is convenient for demoulding and can leave a complete organic gelling material film.
[0065] The drawing rod 3 is located directly above the groove of the steel plate 8. The top of the drawing rod 3 is connected to the drawing drive device, and can be driven by the drawing drive device to achieve height lifting. In this embodiment, the drawing drive device is preferably a servo motor 2, but it can also be replaced by a known drive component in the prior art such as a cylinder.
[0066] The bottom of the drawing rod 3 is preferably coaxially provided with a loading plate 4, and the loading plate 4 is preferably mounted with a stress sensor 5 and a strain sensor 6. The outer diameter of the loading plate 4 is preferably close to or equal to the inner diameter of the first material mold and the second material mold after being assembled.
[0067] The above stress sensor can be used to monitor the pressure value per unit area of the bottom surface of the pull rod 3 in real time.
[0068] The strain sensor can be used to monitor in real time the ratio of the vertical displacement of the pull rod 3 to the thickness of the organic gelling material film.
[0069] In this embodiment, pen70# asphalt to be tested is selected for rapid determination of asphalt cohesive binding energy. Its rheological property parameters include: needle penetration of 67mm (25℃, 5s, 100g), softening point of 47.5℃, elongation of 42.1cm (10℃), dynamic viscosity of 209Pa.s (60℃), density of 1.02g / cm 3 The test temperature is constant at 25°C, and the pull rod 3 rises at a rate of 15 mm / min. 2 The asphalt to be tested and the cylindrical material mold are placed in an oven at a temperature of about 160°C for preheating for no less than 2 hours.
[0070] like Figure 1 As shown, a method for determining the cohesive binding energy of an organic gelling material based on an energy balance method comprises the following steps:
[0071] Step 1: Establish the internal and external energy balance formula of asphalt materials. The formula indicates that the total energy required for the asphalt material to break is equal to the work done by the external force on the asphalt material minus the volume strain energy of the asphalt material, plus the cohesive binding energy of the asphalt material:
[0072]
[0073] Wherein, U represents the total energy required for the asphalt material to break, P represents the external force applied to the asphalt material, Δh represents the displacement of the asphalt along the direction of the external force, ε represents the strain generated by the unit cell of the asphalt material, σ represents the stress generated by the unit cell of the asphalt material, V represents the total volume of the asphalt material, S represents the average cross-sectional area of the asphalt material, and ΔG represents the cohesive bonding energy of the asphalt material.
[0074] Step 2: Prepare the asphalt film: Preheat the asphalt to be tested to 160°C to form a flowable liquid material. According to the formula:
[0075] h=m / ρπr 2
[0076] The asphalt mass required for the test thickness is calculated in reverse, and then the asphalt mass corresponding to the test thickness is poured into a cylindrical material mold preheated to the same temperature as the asphalt to form an asphalt film;
[0077] Step 3: Determine the suitable thickness of asphalt membrane:
[0078] After forming n groups of organic gelling material films (in this step, asphalt films) of different thicknesses according to step 2, a material pull-out strength tester is used to test the pull-out strength of each group of organic gelling material films until the corresponding organic gelling material films are completely broken, and then an organic gelling material film of suitable thickness is selected from the n groups of organic gelling material films of different thicknesses by judging the fracture state on both sides of the fracture surface of the organic gelling material film; a total of x organic gelling material films are selected, and the thickness order is h p1 、h p2 ......h px , wherein x≥3; specifically, selecting an organic gelling material film of suitable thickness from n groups of organic gelling material films of different thicknesses specifically comprises the following steps:
[0079] Step 301, material preparation: According to step 2, this embodiment forms 5 groups of asphalt films with different thicknesses of 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm and 3.5 mm;
[0080] Step 302: compacting the asphalt film:
[0081] A. Place the cylindrical material mold with the asphalt film in step 1 directly below the pull rod 3 of the asphalt pull strength tester.
[0082] B. The pulling rod 3 is lowered until the stress sensor 5 shows a value and stops falling. This indicates that the bottom of the loading plate 4 has touched the top of the asphalt film. Let it stand for at least one hour to keep the temperature of all instruments consistent with the temperature set in the ambient temperature box.
[0083] C. Open the cylindrical asphalt mold outward and remove it.
[0084] Step 303, asphalt film pulling: the pulling rod 3 is raised in height, and the loading plate 4 pulls the asphalt film;
[0085] Step 304, the asphalt film is completely broken: the height of the pull rod 3 continues to rise, and when the actual monitoring value of the stress sensor 5 drops to 0, it is considered that the asphalt film is completely broken;
[0086] Step 305: Determine the fracture state of the material
[0087] A. Take photos to record the fracture surfaces on both sides of the asphalt membrane.
[0088] B. Perform grayscale processing on the images of the fracture surfaces on both sides.
[0089] C. The fracture surfaces of the asphalt membranes with thicknesses of 1.5 mm and 3.5 mm are damaged and have white spots on both sides. The fracture surfaces of the asphalt membranes with thicknesses of 2.0 mm, 2.5 mm and 3.0 mm are intact and have no white spots on both sides. 2.0 mm, 2.5 mm and 3.0 mm are selected as the appropriate thickness h. p1 , hp2 and h p3 .
[0090] Step 4: Asphalt pull-out strength test:
[0091] According to step 2, they are respectively formed into a suitable thickness h p1 、h p2 ......h px After the organic gelling material film (in this step, the asphalt film) is formed, a material pull-out strength tester is used to test the pull-out strength of each group of organic gelling material films until the corresponding organic gelling material film is broken; in this process, a strain-stress curve of the corresponding organic gelling material film is constructed, and the ultimate pull-out strength σ of the organic gelling material is obtained based on the constructed strain-stress curve max As well as the Young's modulus E of the organic cementitious material, the ultimate tensile strength σ of the organic cementitious material max is the stress peak value of the corresponding strain-stress curve, and the Young's modulus E of the organic cementitious material is the slope of the approximate straight line portion of the stress rise curve in the corresponding strain-stress curve; specifically, the asphalt pull-out strength test described in this step includes the following steps:
[0092] Step 401, material preparation: forming into suitable thickness h according to step 2 p1 、h p2 and h p3 Asphalt membrane;
[0093] Step 402, repeating steps 302 to 303 for all the asphalt films formed in step 401;
[0094] Step 403, stress monitoring: during the process of the pull rod 3 rising in height, the stress value per unit area of the bottom surface of the loading plate 4 is monitored in real time by using the stress sensor 5;
[0095] Step 404, strain monitoring: during the process of the pull rod 3 rising in height, the strain sensor 6 is used to monitor in real time the ratio of the vertical displacement of the pull rod 3 to the thickness of the asphalt film;
[0096] Step 405, constructing a strain-stress curve: using the strain monitored in step 404 as the abscissa and the stress monitored in step 403 as the ordinate to establish a strain-stress curve;
[0097] Step 406, obtaining the ultimate tensile strength of asphalt: the height of the pulling rod 3 continues to rise, and the strain-stress curve constructed in step 405 will have a stress peak, which is the ultimate tensile strength of asphalt σ max In this embodiment, three groups of asphalt ultimate pull-out strength σ are obtained max1 , σ max2 and σ max3 ;
[0098] Step 407, internal fracture of the asphalt film: the height of the pulling rod 3 continues to rise. When the actual monitoring value of the stress sensing sensor 5 drops to 10% of the maximum pressure peak, it is considered that the internal fracture of the asphalt film occurs, and the height of the pulling rod 3 stops rising. At this time, the slope of the approximate straight line part of the stress rise curve in the stress-strain curve is taken as the asphalt Young's modulus E. In this embodiment, three groups of asphalt Young's moduli E1, E2 and E3 are obtained.
[0099] Step 5: Based on step 1, step 4 and Griffith energy balance theory, calculate the cohesive binding energy of the organic gelling material. The specific process is as follows:
[0100] Step 501: Establishing a calculation formula for the cohesive binding energy of organic gelling materials
[0101] A. Substitute the following formula into the asphalt material internal and external energy balance formula established in step 1:
[0102] Δh=Ph / πEr 2
[0103] σ=P / πr 2
[0104] ε=P / πEr 2
[0105] V=πr 2 h
[0106] S=πr 2
[0107] The formula is as follows:
[0108]
[0109] B. According to Griffith's energy balance theory, when the internal fracture of the material occurs, the material is in a state of equilibrium and the total energy does not change, that is, the formula:
[0110]
[0111] In the formula, Represents partial differential.
[0112] C. Get the formula:
[0113]
[0114] In the formula, △G y is the asphalt cohesive binding energy corresponding to the yth suitable thickness, σ maxy is the ultimate tensile strength of asphalt corresponding to the yth suitable thickness, h py is the suitable thickness of the yth asphalt film, E y is the Young's modulus corresponding to the yth suitable thickness, y = 1, 2 and 3; in the actual test process, the pull-out strength of the organic gelling material will be affected by the film thickness, but the cohesive binding energy of the organic gelling material has nothing to do with the thickness of the organic gelling material film. Therefore, before the test, the present invention has performed curve fitting for the calculated cohesive binding energy of the organic gelling material film of different thicknesses to obtain the calibration coefficient
[0115]
[0116] In the formula, λ y is the calibration coefficient corresponding to the yth suitable thickness, and a and b are unknown coefficients.
[0117] D. The calculation formula of the calibrated asphalt cohesive binding energy is as follows
[0118]
[0119] Step 502, solve the unknown coefficients a and b: Based on step 501, with λ y is the independent variable, ΔG y As the dependent variable, the variance of the three asphalt cohesive binding energies is minimized as the optimization goal, and the nonlinear programming solution is performed in EXCEL software to obtain the unknown coefficients a and b;
[0120] Step 503, calculate the cohesive binding energy of asphalt: substitute the unknown coefficients a and b obtained in step 502 into the calculation formula in step 501, and take the average value of the three cohesive binding energies of asphalt as the cohesive binding energy of the asphalt.
[0121] The preferred embodiments of the present invention are described in detail above; however, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, various equivalent transformations can be made to the technical solutions of the present invention, and these equivalent transformations all belong to the protection scope of the present invention.
Claims
1. A method for determining the cohesive binding energy of an organic gelling material based on an energy balance method, characterized in that: The steps include: Step 1: Establish the internal and external energy balance formula of organic gelling materials: Wherein, U represents the total energy required for the fracture of the organic gelling material, P represents the external force applied to the organic gelling material, Δh represents the displacement of the organic gelling material along the direction of the external force, ε represents the strain generated by the unit cell of the organic gelling material, σ represents the stress generated by the unit cell of the organic gelling material, V represents the total volume of the organic gelling material, S represents the average cross-sectional area of the organic gelling material, and ΔG represents the cohesive binding energy of the organic gelling material; Step 2, preparing an organic gelling material film: first preheat the organic gelling material to be tested to the melting temperature to form a flowable liquid material, and then pour the liquid material into a cylindrical material mold preheated to the same temperature as the material to form an organic gelling material film; wherein the cylindrical material mold can be opened and closed and dismantled, and the inner diameter is r; the mass of the poured organic gelling material is m, and the density is ρ; the thickness h of the organic gelling material film can be controlled by the following formula: h=m / ρπr 2 ; Step 3, determining the suitable thickness of the organic gelling material film: after forming n groups of organic gelling material films of different thicknesses according to step 2, use a material pull-out strength tester to test the pull-out strength of each group of organic gelling material films formed until the corresponding organic gelling material film is completely broken, and then judge the fracture state on both sides of the fracture surface of the organic gelling material film to select an organic gelling material film of suitable thickness from the n groups of organic gelling material films of different thicknesses; a total of x organic gelling material films are selected, and the thickness order is h p1 、h p2 ……h px , where x≥3; Step 4: Pull-out strength test of organic cementitious materials: Form the organic cementitious materials into appropriate thickness h according to step 2. p1 、h p2 ……h px After the organic gelling material film is formed, a material pull-out strength tester is used to test the pull-out strength of each group of organic gelling material films until the corresponding organic gelling material film is broken; in this process, a strain-stress curve of the corresponding organic gelling material film is constructed, and the ultimate pull-out strength σ of the organic gelling material is obtained based on the constructed strain-stress curve max As well as the Young's modulus E of the organic cementitious material, the ultimate tensile strength σ of the organic cementitious material max is the peak stress value of the corresponding strain-stress curve, and the Young's modulus E of the organic cementitious material is the slope of the approximate straight line portion of the stress rising curve in the corresponding strain-stress curve; Step 5: Based on step 1, step 4 and Griffith energy balance theory, calculate the cohesive binding energy of the organic gelling material. The specific process is as follows: Step 501: Establish a calculation formula for the cohesive binding energy of the organic gelling material. The specific formula is as follows: In the formula, ΔG y is the cohesive binding energy of the organic gel material corresponding to the yth suitable thickness, λ y is the calibration coefficient corresponding to the yth suitable thickness, a and b are unknown coefficients, σ maxy is the ultimate tensile strength of the organic cementitious material corresponding to the yth suitable thickness, h py is the thickness of the organic gelling material film corresponding to the yth suitable thickness, E y is the Young's modulus corresponding to the yth suitable thickness, y = 1, 2...m; Step 502, solve the unknown coefficients a and b: Based on step 501, with λ y is the independent variable, ΔG y As the dependent variable, and taking the minimum variance of the cohesive binding energy of m organic gelling materials as the optimization goal, it is substituted into the numerical calculation software for nonlinear programming solution to obtain the unknown coefficients a and b; Step 503, calculating the cohesive binding energy of the organic gelling material: Substitute the unknown coefficients a and b obtained in step 502 into the calculation formula in step 501, and take the average value of the cohesive binding energy of x organic gelling materials as the cohesive binding energy of the organic gelling material.
2. The method for determining the cohesive binding energy of organic gelling materials based on the energy balance method according to claim 1, characterized in that: In step 3, the thickness of the organic gelling material film is determined, which specifically includes the following steps: Step 301, material preparation: forming n groups of organic gelling material films of different thicknesses according to step 2; Step 302, compacting the organic gelling material film: placing the cylindrical material mold with the organic gelling material film directly below the drawing rod of the material pulling strength tester; the drawing rod is lowered, and the loading plate at the bottom of the drawing rod compacts the top surface of the organic gelling material film; then, the cylindrical material mold is removed in an opening and closing manner; Step 303, pulling the organic gelling material film: the pulling rod is raised, and the loading plate pulls the organic gelling material film; Step 304, the organic gelling material film is completely broken: the height of the pull plate rod continues to rise, and when the actual monitoring value of the stress sensor drops to 0, it is considered that the organic gelling material film is completely broken; Step 305, determine the fracture state of the material: take photos to record the fracture surfaces on both sides of the organic gelling material film; perform grayscale processing on the image; if the fracture surfaces on both sides are complete and have no white spots, it is considered that the fracture only occurs inside the organic gelling material film, and the corresponding thickness of the organic gelling material film is taken as the appropriate thickness h p If any fracture surface is damaged and has white spots, repeat steps 301 to 305 until x different suitable thicknesses h are obtained. p1 、h p2 ……h px ; where x≥3.
3. The method for determining the cohesive binding energy of organic gelling materials based on the energy balance method according to claim 2, characterized in that: In step 4, the organic cementitious material tensile strength test specifically includes the following steps: Step 401, material preparation: forming into suitable thickness h according to step 2 p1 、h p2 ……h px Organic gelling material film; Step 402, repeating steps 302 to 303 for all the organic gelling material films formed in step 401; Step 403, stress monitoring: during the process of the pull rod rising in height, a stress sensor is used to monitor the stress value per unit area of the bottom surface of the loading plate in real time; Step 404, strain monitoring: during the process of the pull rod rising in height, a strain sensor is used to monitor in real time the ratio of the vertical displacement of the pull rod to the thickness of the asphalt film; Step 405, constructing a strain-stress curve: using the strain monitored in step 404 as the abscissa and the stress monitored in step 403 as the ordinate to establish a strain-stress curve; Step 406, obtaining the ultimate pull-out strength of the organic gelling material: the height of the pull-out rod continues to rise, and the strain-stress curve constructed in step 405 will have a stress peak value, which is the ultimate pull-out strength σ of the organic gelling material obtained. max ; Step 407, internal fracture of the organic gelling material film: the height of the pulling rod continues to rise. When the actual monitoring value of the stress sensing sensor drops to 10% of the maximum pressure peak, it is considered that the organic gelling material film is fractured and the height of the pulling rod stops rising. At this time, the slope of the approximate straight line portion of the stress rise curve in the stress-strain curve is taken as the Young's modulus E of the organic gelling material.
4. The method for determining the cohesive binding energy of organic gelling materials based on the energy balance method according to claim 3, characterized in that: In step 2, the preheating temperature of the tested organic gelling material is the same as the preheating temperature of the cylindrical material mold, and both are not lower than the melting temperature of the organic gelling material.
5. The method for determining the cohesive binding energy of organic gelling materials based on the energy balance method according to claim 3, characterized in that: In step 3 and step 4, the drawing of the organic cementitious material needs to be carried out in a constant temperature environment maintained at the test temperature ±5°C.
6. The method for determining the cohesive binding energy of organic gelling materials based on the energy balance method according to claim 5, characterized in that: In step 3 and step 4, the test temperature for drawing the organic gelling material cannot be higher than the melting point of the organic gelling material, nor lower than its glass transition temperature.
7. The method for determining the cohesive binding energy of organic gelling materials based on the energy balance method according to claim 3, characterized in that: In step 3 and step 4, the height rising rate of the pull rod is in the range of 10 to 20 mm / min.
8. The method for determining the cohesive binding energy of organic gelling materials based on the energy balance method according to claim 3, characterized in that: In step 1, the cylindrical material mold includes a first material mold and a second material mold with two openings arranged opposite to each other and both in a semicircular shape.
9. The method for determining the cohesive binding energy of organic gelling materials based on the energy balance method according to claim 8, characterized in that: The cylindrical material mold is placed on a steel plate with a groove on the top surface; wherein the first material mold and the second material mold are both located in the groove of the steel plate and can be opened and closed relative to each other.
10. The method for determining the cohesive binding energy of organic gelling materials based on the energy balance method according to claim 9, characterized in that: The outer sides of the first material mold and the second material mold are both provided with radial pull rods, and the ends of the pull rods slide through the side walls of the grooves of the steel plates; by pulling the pull rods, the first material mold and the second material mold can be relatively opened and closed.